1998
DOI: 10.1093/jmedent/35.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Tortoise Tick Amblyomma marmoreum (Acari: Ixodidae) on a Reptile-Breeding Facility in Florida

Abstract: The tortoise tick Amblyomma marmoreum Koch was found to be established on a reptile facility in central Florida. Over a 5-mo period, 443 ticks were collected from tortoises, dogs, and vegetation. Collections from hosts were primarily from 3 species of exotic tortoises, including leopard tortoises, Aldabra tortoises, and yellow-footed tortoises. The total numbers of ticks present, the presence of all life stages, and the slow development of this species indicate that this is not a recent infestation. The source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 0 publications
0
18
0
3
Order By: Relevance
“…It has been estimated that if the disease were introduced into Florida, one of the largest beef producers in the United States, up to 50% of infected cattle and 90% of infected sheep, goats and deer would die of the disease (Burridge, 1997; Burridge et al ., 2000). Breeding colonies of the African species A. variegatum and A. marmoreum have already been found in reptile holding centres in Miami (Allan et al ., 1998). Exotic ticks have been identified on 29 (91%) of 32 reptile premises in 18 counties of Florida (Burridge et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that if the disease were introduced into Florida, one of the largest beef producers in the United States, up to 50% of infected cattle and 90% of infected sheep, goats and deer would die of the disease (Burridge, 1997; Burridge et al ., 2000). Breeding colonies of the African species A. variegatum and A. marmoreum have already been found in reptile holding centres in Miami (Allan et al ., 1998). Exotic ticks have been identified on 29 (91%) of 32 reptile premises in 18 counties of Florida (Burridge et al ., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of introduction of heartwater into the United States through the international trade in live reptiles was emphasized by the results of three of our recent studies. First, we found that two of the imported reptilian tick species that have been reported to be experimental vectors of heartwater, A. marmoreum and A. sparsum , have become established in Florida,4,5 although subsequent actions have successfully eradicated the known established infestations 5. Second, we demonstrated convincingly that A. marmoreum ticks that had originated from infested reptiles on premises in Florida are competent experimental vectors of C. ruminantium 6.…”
Section: Risks Associated With International Trade In Live Reptilesmentioning
confidence: 65%
“…In 1997, a leopard tortoise, Geochelone paradalis Bell, was brought to the Veterinary Medical Teaching Hospital of the University of Florida, Gainesville, FL, and ticks, identiÞed subsequently as A. marmoreum, were removed from the animal (Allan et al 1998). When the reptile breeding facility from which the tortoise originated was visited to determine if it was infested with the tick, a total of 443 A. marmoreum was collected from tortoises (53.3%), dogs (1.1%), and vegetation (45.6%).…”
Section: Successful Eradicationmentioning
confidence: 99%
“…Other transport hosts of exotic arthropods include the elephant, Elephas maximus L., cheetah, Acinonyx jubatus (Schreber), sloths, antelopes of several species, and a bat-eared fox, Otocyon megalotis (Demarest). Imported reptiles, which have not been regulated, have also served as hosts for the introduction and establishment of exotic arthropods (Allan et al 1998).…”
mentioning
confidence: 99%